Solar panel installation feasibility analysis based on techno-economic of PVSyst at Universitas Multimedia Nusantara - Rinanda Saputri, Fahmy; Dimas Paramasatya, Johanes; Maliki Akbar, Agie (Bulletin of Electrical Engineering and Informatics, 2025)
Universitas Multimedia Nusantara (UMN) integrates green building principles to enhance environmental sustainability by reducing energy waste and utilizing renewable energy sources. This study conducts a feasibility analysis of installing solar panels in a green open space near building D to supply up to 20% of its electricity needs. PVSyst simulations evaluated different panel orientations (north, south, and east). The results indicated that the installation is currently unfeasible, with a net present value (NPV) of -134,346,450.22 IDR and an internal rate of return (IRR) of -4.64%. The challenges included shading from surrounding buildings, heat buildup, and limited installation space. To improve viability, future installations should focus on sites with minimal shading and explore advanced technologies to enhance efficiency. Additionally, optimizing panel orientation and investigating alternative renewable energy sources suited to UMN’s conditions are crucial. These measures can enhance the effectiveness of solar installations and contribute to overall energy sustainability on campus.